REFORMASI SISTEM REKRUTMEN PEJABAT DALAM BIROKRASI PEMERINTAH - Muhammad Nasir (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
This paper investigates the reformation in recruitment system for Echelon II positions in Aceh government.The reformation process occupied the use of fit and proper test as a transparence and accountably processin selecting public servants. The selection process was also open for the public where every civil servantwith certain condition and grade can participate. This way of selection process accommodates well the bestcandidates in filling appropriate positions in Provincial Dinas. So far, the follow up of the selection processwas the performance evaluation which contains certain indicators.Key words: reformation, fit and proper test, civil servants, echelon II